Glial Cells in Amyotrophic Lateral Sclerosis - Jurate Lasiene; Koji Yamanaka (Neurology Research International)
Amyotrophic lateral sclerosis (ALS) is an adult motor neuron disease characterized by premature death of upper and lower motor neurons. Two percent of ALS cases are caused by the dominant mutations in the gene for superoxide dismutase 1 (SOD1) through a gain of toxic property of mutant protein. Genetic and chimeric mice studies using SOD1 models indicate that non-neuronal cells play important roles in neurodegeneration through non-cell autonomous mechanism. We review the contribution of each glial cell type in ALS pathology from studies of the rodent models and ALS patients. Astrogliosis and microgliosis are not only considerable hallmarks of the disease, but the intensity of microglial activation is correlated with severity of motor neuron damage in human ALS. The impaired astrocytic functions such as clearance of extracellular glutamate and release of neurotrophic factors are implicated in disease. Further, the damage within astrocytes and microglia is involved in accelerated disease progression. Finally, other glial cells such as NG2 cells, oligodendrocytes and Schwann cells are under the investigation to determine their contribution in ALS. Accumulating knowledge of active role of glial cells in the disease should be carefully applied to understanding of the sporadic ALS and development of therapy targeted for glial cells.